2008
DOI: 10.3354/meps07409
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends in condition of Atlantic cod Gadus morhua on the Icelandic shelf

Abstract: Interannual (1993Interannual ( to 2006, spatial and bathymetric trends in the hepatosomatic index (H) and relative body condition index (Kr) of Atlantic cod Gadus morhua in Icelandic waters were investigated from data collected during annual spring (March) groundfish surveys. Individual stomach content data were analysed to assess the relationship between condition and consumption of capelin Mallotus villosus. Liver condition was found to vary with region and depth, tending to be highest in deeper water and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 57 publications
4
46
1
Order By: Relevance
“…Appetite may actually be suppressed at low temperature, leading to a decrease in condition (Jobling 1988, Morgan 1992. However, other studies have found little or no effect of temperature on condition (Yaragina & Marshall 2000, Yoneda & Wright 2005a, Pardoe et al 2008. Changes in the abundance and type of prey available with varying temperature can also influence condition.…”
Section: Discussionmentioning
confidence: 96%
“…Appetite may actually be suppressed at low temperature, leading to a decrease in condition (Jobling 1988, Morgan 1992. However, other studies have found little or no effect of temperature on condition (Yaragina & Marshall 2000, Yoneda & Wright 2005a, Pardoe et al 2008. Changes in the abundance and type of prey available with varying temperature can also influence condition.…”
Section: Discussionmentioning
confidence: 96%
“…However, mature cod have been found to have higher liver condition than immature cod (Eliassen and Vahl 1982b;Vitale et al 2006;Pardoe et al 2008), suggesting that better condition may be the consequence, rather than cause, of maturation (Rijnsdorp 1990). If this is the case, it could mean the false interpretation of a positive effect of condition on maturation probability (Grift et al 2007), and should therefore be considered in future experimental investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that changes in condition are responsible for the overall downward trend in maturation, although it is feasible that short-term variation in condition (Pardoe et al 2008) may have contributed to the observed variability in Lp50s. In four previous PMRN studies, of plaice (Pleuronectes platessa, Grift et al 2007), sole (Solea solea, Mollet et al 2007), and Atlantic cod in the Baltic (Vainikka et al 2009) and off Newfoundland (Baulier et al 2006), inclusion of condition as a third explanatory variable of maturation probability did not alter the conclusion of a decreasing temporal trend in the PMRN midpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine seasonal and spatial variations in feeding activity and nutritional status of Japanese flounder, we determined the stomach content index (SCI), hepatosomatic index (H), and relative condition factor (Kr) (Pardoe et al 2008) in 4 size classes (20.0-29.9, 30.0-39.9, 40.0-49.9, and ≥50.0 cm TL) as follows:…”
Section: Methodsmentioning
confidence: 99%